2014
DOI: 10.1017/s1463423614000309
|View full text |Cite
|
Sign up to set email alerts
|

Negative/positive home-based caregiving appraisals by informal carers of the elderly in Japan

Abstract: With respect to care burden, positively associated factors were sekentei or social pressure [odds ratio (OR) 4.25, 95% confidence interval (CI) 1.39-13.04], caregiving obligation (OR 3.11, 95% CI 1.43-6.77), spouse carer (OR 2.58, 95% CI 1.05-6.35), daughter-in-law carer (OR 3.68, 95% CI 1.31-10.34), and depression (OR 50.58, 95% CI 13.85-184.67). With respect to positive appraisal, negatively associated factors were caregiving obligation (OR 0.29, 95% CI 0.15-0.53), male carer (OR 0.44, 95% CI 0.21-0.92), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Nonetheless, caregiver's appraisal of their daily caregiving life is an important source of such information which may change during the course of their chronic disease trajectory. Therefore, it is important to assess older spouse caregivers’ perceived stress at every available opportunity (Imaiso, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, caregiver's appraisal of their daily caregiving life is an important source of such information which may change during the course of their chronic disease trajectory. Therefore, it is important to assess older spouse caregivers’ perceived stress at every available opportunity (Imaiso, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, only three modifiable factors were identified: family functioning, quality of the caregiver and care recipient dyadic relationship, and support from the family (DiBartolo & Soeken, 2003;Gupta & Bowie, 2018;Hanks et al, 2007;Liu & Huang, 2018;Pruchno & Patrick, 1999;Whitney et al, 2007). Family caregiving obligation was the nonmodifiable factor identified (Imaiso, 2015;Lee et al, 2010).…”
Section: Factors At the Interpersonal Levelmentioning
confidence: 95%
“…Modifiable factors relevant to the caregivers were most well studied. The number of studies on caregiver health ranked highest, including both the perceived physical health and psychological health (depressive symptoms, anxiety, positive/negative affect) (Affinito, 2018;Brickell et al, 2018;Gonyea, O'Connor, Carruth, & Boyle, 2005;Imaiso, 2015 & Brown, 2018;McAuliffe, Ong, & Kinsella, 2018;Pruchno & Patrick, 1999;Rapp & Chao, 2000;Verbakel et al, 2018;Zhang & Zhao, 2011).…”
Section: Factors At the Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hav-ing very few close friends was associated with a significantly higher likelihood of major depression among rural residents compared to urban residents. It is suggested that the important issues might be what the whole community (ie, urban or rural) understands about the life of the people, rather than the views of the actual communities that the people live in [17]. The findings in the current study suggest that social function might be a more important outcome measure of elderly health, particularly regarding mental health or depression, when considering outcome measures for effective integrated community care that takes into account the characteristics of each community.…”
Section: Discussionmentioning
confidence: 99%